Mechanisms and Efficacy of Traditional Chinese Medicine in Heart Failure - Wang, Anzhu; Zhao, Wei; Yan, Kaituo; Huang, Pingping; Zhang, Hongwei; Zhang, Zhibo; Zhang, Dawu; Ma, Xiaochang (Frontiers in Pharmacology, 2022)
Heart failure (HF) is one of the main public health problems at present. Although some breakthroughs have been made in the treatment of HF, the mortality rate remains very high. However, we should also pay attention to improving the quality of life of patients with HF. Traditional Chinese medicine (TCM) has a long history of being used to treat HF. To demonstrate the clinical effects and mechanisms of TCM, we searched published clinical trial studies and basic studies. The search results showed that adjuvant therapy with TCM might benefit patients with HF, and its mechanism may be related to microvascular circulation, myocardial energy metabolism, oxidative stress, and inflammation.